2020
DOI: 10.4236/jbm.2020.88015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Nutritional Status and Phytomedicinal Properties of Dried Rhizomes of Turmeric (<i>Curcuma longa</i>)

Abstract: Turmeric (Curcuma longa) belongs to the family Zingiberaceae and has long been used traditionally for centuries as a spice and medicinal elixir. Hence, the present study aimed to profile the nutritional and phytomedicinal properties of the plant in order to justify its relevance in traditional phytomedicine and advocate its application in novel pharmacological products. Using standard methods (High Performance Liquid Chromatography, Gas Chromatography-Mass Spectroscopy and Atomic Absorption Spectrophotometry),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
5
1
Order By: Relevance
“…The highest level of potassium (815.28 mg/g) was observed in ginger powder (GP) while the cloves powder (CP) had the least value (129.35 mg/g). These values are higher than the reports of [24] and [49] for potassium contents of ginger (0.72 mg/g) and turmeric (9.24 mg/g). The potassium contents of clove (0.39 mg/g) and turmeric (2.49 mg/g) reported by [21] are lower than the values obtained for samples in this study while [43] reported (0.42 mg/g) for potassium content of ginger powder.…”
Section: Resultscontrasting
confidence: 80%
“…The highest level of potassium (815.28 mg/g) was observed in ginger powder (GP) while the cloves powder (CP) had the least value (129.35 mg/g). These values are higher than the reports of [24] and [49] for potassium contents of ginger (0.72 mg/g) and turmeric (9.24 mg/g). The potassium contents of clove (0.39 mg/g) and turmeric (2.49 mg/g) reported by [21] are lower than the values obtained for samples in this study while [43] reported (0.42 mg/g) for potassium content of ginger powder.…”
Section: Resultscontrasting
confidence: 80%
“…Other elements like: K, Zn, Ag, As, Cd, Co, Cu, Ni and Pb were found to be present in very small quantities that are not significant (Table 1). Enemor et al [20] study shows that Curcuma longa rhizomes had higher contents of calcium, magnesium, potassium and sodium in parts per million (ppm) at 38.68 ± 0.114, 19.75 ± 0.001, 9.20 ± 0.002 and 7.06 ± 0.014 respectively. Their result is similar to the result obtained in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This decrease might be a result of the phytomedicinal, mineral, and vitamin constituents of breadfruit. It has earlier been revealed that medicinal plants contain sufficient phytochemicals responsible for their beneficial properties both in nutrition and disease management [20,21].…”
Section: Discussionmentioning
confidence: 99%